Issuance requirements of electronic money within the framework of the Islamic banking system - Yaiche Temem , Chaouki; Saouli, zohra (Revue jurisprudence, 2019)
Electronic money is an advanced form of payment instrument. It is considered as a means of obtaining goods and services as an acceptable store of value. The role of the state represented by the central bank as legally authorized to issue money. This new form, which requires to take into consideration a number of legislative and regulatory rules Induced from the rules of dealing in the field of electronic banking and the rules of Islamic banking, especially for countries that rely on it as a method to ensure the legitimate circulation of this method In the field of payment.